Rare earth elements, suspenden particulate matter,dissolved organic carbon, Neodymium/Ytterbium ratio and Neodymium isotopes data along the salinity gradient in the Changjiang estuary - Hong Che; Zhang Jing; Liu Qian; He Huijun; Zhao Zhi-Qi (PANGAEA, 2021)
Surface seawater samples from the Changjiang Estuary were collected during the high discharge season in August 2015. The sampling locations focused on the Changjiang River Estuary area from ~32N to ~29N . Soon after their recovery, all of the samples were filtered through a 0.40-μm Whatman membrane onboard the vessel. The samples were then acidified to a pH of ~2 with high-purity HCl . From each sample, 15-20 L was placed in acid-cleaned bottles for Nd isotope composition analysis, and 500 mL was collected to determine the REE concentration. The filter membranes were cryopreserved for the determination of SPM. REE concentrations and Nd isotope compositions determined in these filtered waters were treated as dissolved-phase measurements (Nd<0.45μm). An unfiltered water sample was directly acidified to a pH <2 with hydrochloric acid after sample collection and then filtered through a 0.40-μm Whatman membrane in a cleanroom to determine the acid-soluble REEs (Nd>0.45μm) The data on dissolved REE concentrations were measured by ICP-MS (Thermo iCAP-Q) with a precision of better than 4% and a reagent blank of less than 2%, based on the results of replicated measurements. Nd isotope measurements were made on Nu plasma I and II instruments at the Key Laboratory of Environmental Geochemistry. Corrections were made for instrumental mass bias using a value of ^1?^3Nd/^1??Nd = 0.7219. The ^1?^3Nd/^1??Nd ratios of the samples were normalized using the accepted value from the literature of 0.512115±0.000006 (Tanaka et al., 2000) for JNdi-1 (Geological Survey of Japan). Blank values were ≤700 pg (representing an average of 2% of the sampled signal). The Nd isotopic compositions can be expressed by ε~Nd~ = ^1?^3Nd/^1??Nd[measured] / ^1?^3Nd/^1??Nd[CHUR]-1) exttimes10000, where CHUR stands for the Chondritic Uniform Reservoir, with a value is 0.512638 (Wasserburg et al., 1981), and ^1?^3Nd/^1??Nd[measured] represents the measured value.